Utilization Of Discord Bots In Providing Manhwa Recommendations Using Content-Based Filtering Method - Muhammad Farhan Maulana; Ani Dijah Rahajoe; Made Hanindia Prami Swari (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
The high number of manhwa released today makes it difficult for readers to find manhwa that match their preferences, especially when trying to find manhwa that are similar to ones they have read before. The manual search process, either through recommendations from communities or online forums, often results in subjective and inconsistent suggestions. To address this issue, a Discord bot was developed that utilizes the Content-Based Filtering method as an automated solution to manhwa recommendation. This method uses the Cosine Similarity algorithm to measure the similarity between manhwa based on features such as title, genre, synopsis, and author. For comparison, the Euclidean Distance algorithm is used to evaluate the accuracy and performance of the recommendation. From the test results, the Cosine Similarity algorithm showed superior performance in providing recommendations based on the questionnaire results and showed a high level of user satisfaction with the developed Discord bot.